2021
DOI: 10.1161/circresaha.119.316386
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Electrical Remodeling Underlies Atrioventricular Block in Athletes

Abstract: Rationale: Athletes present with atrioventricular node (AV node) dysfunction manifesting as AV block. This can necessitate electronic pacemaker implantation, known to be more frequent in athletes with a long training history. Objective: AV block in athletes is attributed to high vagal tone. Here we investigated the alternative hypothesis that electrical remodeling of the AV node is responsible. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 79 publications
5
52
0
Order By: Relevance
“…To our knowledge, a single study, conducted in our laboratory, evaluated the effect of training on 2AVB in a small group of horses, where a difference between trained and untrained horses was not identified and the types of 2AVB were not classified. However, in this study the trained horses had longer PR intervals, which supported altered AV conduction, possibly caused by intrinsic remodeling within the AV node 16 …”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…To our knowledge, a single study, conducted in our laboratory, evaluated the effect of training on 2AVB in a small group of horses, where a difference between trained and untrained horses was not identified and the types of 2AVB were not classified. However, in this study the trained horses had longer PR intervals, which supported altered AV conduction, possibly caused by intrinsic remodeling within the AV node 16 …”
Section: Introductionsupporting
confidence: 49%
“…56 In parallel, we previously documented prolongation of the PR interval that persisted in trained horses compared to untrained horses after simultaneous pharmacological blockage of both the sympathetic and parasympathetic nervous systems. 16 Also we identified down-regulation of important pacemaker ion channels, including the hyperpolarizationactivated cyclic nucleotide-gated channel 4 (HCN4) and the L-type calcium channels (Cav1.2) within the AV node in trained horses, which could be responsible for the slowed AV conduction seen in both human and equine athletes. 16…”
Section: Effect Of Training On Atrioventricular Conduction In Horsesmentioning
confidence: 97%
“…Finally, Bidaud et al demonstrate that genetic ablation of G-protein-gated inwardly rectifying potassium channels (responsible for I KAch current) counteracts slowed pacemaking induced by exercise training in mice by preventing transcriptional and electrical remodelling of pacemaking ion channels. This work builds on findings by D’Souza and Boyett demonstrating that a microRNA network orchestrates reduced sinus node ion channel expression in a range of situations where dysfunctional pacemaking is observed, including exercise training ( D'Souza et al, 2014 ; D'Souza et al, 2017 ; Mesirca et al, 2021 ) and heart failure ( Yanni et al, 2020 ). Based on the observations ranging from the whole animal to the microRNA, coupled with previous work by the team ( Mesirca et al, 2014 ; Mesirca et al, 2016 ) it is concluded that I KAch modulation may be an effective pharmacological strategy for SND rescue.…”
mentioning
confidence: 62%
“…[ 38 ] More recently, evidence suggests significant electrical remodelling within the sinus node, with downregulation of potassium/sodium hyperpolarisation activated cyclic nucleotide-gated channel 4 (HCN-4). [ 39 , 40 ] A possible dose–response relationship has also been suggested, with a study of cross-country skiers demonstrating that those who participated in more races had a higher risk of sinus node disease or third-degree atrioventricular block. [ 24 ]…”
Section: Bradyarrhythmiasmentioning
confidence: 99%